THE EFFECTIVENESS OF USING NATURAL APPROACH TO IMPROVE STUDENTS’ INTERACTION ABILITY AT THE SECOND GRADE OF SMAN 4 PINRANG - Desy Lestary; Anwar Sani (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
This research aimed to know-how is the effectiveness of using Natural Approach to improve students? interaction ability. Students should have an ability to build interaction in order to actualize the function of language as device communication which occurs within classroom activity and create an interactive teaching and learning process so it must be considered to be improved. This study employed a collaborative classroom action research design where the writer and collaborator work together in conducting this study. The subject of this research was the 25 students of XI IPA 1 at SMAN 4 Pinrang in the academic year 2018-2019. This study was carried out in two cycles which conducted in three meetings for each cycle by taking classroom action research phases i.e. planning, action, observation, and reflection. This study was descriptive qualitative research which used observation checklist, interview, and questionnaire as instruments of collecting data. The result after analyzing data qualitatively showed that (1) by using Natural Approach, students could participate in performing instructions and conveying responses during teaching and learning process. (2) They were active in giving feedback, answering questions, moreover, doing interaction within classroom activity. (3) Every class activity of each Comprehension (Pre-production), Early Production, and Speech Emergence stages in the two cycles encouraged them to involve actively in the teaching and learning process. Those descriptions indicate the effectiveness of using Natural Approach to improve students? interaction ability.